Implications of Postponed General Election on the Term of Office of the President and Vice President in Indonesian Statehood - Rayhan Naufaldi Hidayat; Abel Parvez (IHSA Institute, 2022)
This study discusses the postponement of the general election and its implications for the terms of office of the President and Vice President in terms of Indonesian constitution. The purpose of this study is to examine the constitutionality of postponing the general election and its correlation with the term of office of the President and Vice President in the constitution. The research method used is normative legal research through a statutory approach. The results of this study indicate that postponing general elections when the state is in normal conditions is contrary to the constitution and has violated democratic principles. However, the postponement of the general election may occur if the country is in a state of emergency. The constitution itself has not yet regulated it, thus creating a legal vacuum that leads to ambiguity in the positions of President and Vice President. Therefore, this research provides a solution so that state sovereignty is maintained and constitutional democracy is not injured